Cambodian Dollarization : Its Policy Implications for LDCs' Financial Development. - Okuda, Hidenobu. (Taylor & Francis Group, 2023)
This book is the first study to provide a comprehensive picture of the reality and structure of dollarization in Cambodia, which has been achieving rapid economic and financial development since the 2000s. It uses data collected through nationwide surveys conducted by the National Bank of Cambodia and JICA Ogata Sadako Research Institute.